Hubungan Asupan Vitamin A, Seng Dan Pendidikan Ibu Dengan Kejadian Pneumonia Pada Balita Di Puskesmas Tawangsari Sukoharjo - Fitria Nurmawati, Ery; , Muwakhidah, SKM., M.Kes; , Kristien A, SKM., M.Si (2015)
Introduction: Toddlers have immune systems that are still susceptible to various diseases. Pneumonia which is an acute respiratory infections (ARI) is a disease that can cause death in children. There are many determinants of pneumonia including vitamin A intake, zinc intake and mothers education. Objective: The purposes of this research were to assess the correlations between vitamin A intake, zinc intake and mothers education and pneumonia in children at Primary Health Service of Tawangsari Sukoharjo. Research method: This research used observational with cross-sectional design. The respondents were children aged 7-59 months. Sampling used consequtive sampling technique. Pneumonia status data were obtained using ARY timer. Vitamin A intake and Zinc intake data were obtained using 24 hour food recall and mothers education data were obtained through interview. Statistical test using Chi-Square correlation test with alternative Fisher's Exact test. Results: Toddler suffering from pneumonia was 27,3%. Zinc intake in toddler was mostly normal (70,5%). Vitamin A intake in toddler was mostly normal (70,5%). Most mothers' education was basic education (65,9%). Based on the Fisher's Exact, there was correlations between intake of vitamin A, Zinc and mothers education and pneumonia in children (p< 0,005). Conclusion: There were correlations between intake of vitamin A, Zinc and mothers education and pneumonia in children at primary health service of Tawangsari Sukoharjo.